The utilization of marigold (Tagetes erecta L.) for traditional ceremonies in Indonesia: A systematic review - Raihandhany, Reza; Kurniawan, Bima (Genbinesia Journal of Biology, 2023)
Ethnobotanical heritages in Indonesia are exceptionally diverse because of the multicultural, multi-religious practice, and acculturation between them. The mega-biodiverse island nation is home to more than 800 ethnicities and naturally acts as sanctuary for the lush tropical ecosystems and its inhabitants. The hospitable nature of Indonesian land provides asylum for numbers of plants, including non-native species. Marigold (Tagetes erecta), a non-native ornamental plant that exhibits distinct showy flowers is cultivated and extensively grown in Indonesian lands. Beside being used as ornamental plants, some of the local communities are using marigold as a part in conducting their traditional ceremonies. This article provides some recorded traditional usage of marigold in traditional ceremonies of Indonesian communities from scientific articles. Significant usages of marigold are notably practiced by Hindu communities in Bali, Java (Tengger) and Lombok as part of their respective traditional-religious ceremonies. Vibrant color of the flower, its availability throughout the year, and easiness of cultivation are desirable traits that keep marigold usages significant. Local beliefs value marigold’s prominent flower color because it represents their Lord. The presence of marigold and its significant usage in the local communities provides space for native species to grow.